Kesesuaian Kompetensi dan Area Kerja Perawat Rawat Jalan - Ali Ahmad Keliobas; Hanny Handiyani; Tuti Afriani; Cori Tri Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the implementation of the clinical authority of nurses in outpatient units based on the level of competence of nurses. The research method used is a case study (identification of problems, problem analysis and problem priority setting, preparation of Plan of Action (POA), implementation and evaluation). The results showed that the performance of clinical authority by nurses according to the level of the career path they had, namely nurses with PK I level of clinical authority were sometimes carried out (66.7%), PK II Medical Surgery (50%) and PK III Medical (57.1%) levels of authority. Clinically, it is rarely performed, at the level of PK III, the clinical authority is often performed (60%), at the PK III level, the clinical authority is emergency (100%), the PK III level is Neuroscience. Clinicians often do it (50%) and the PK III, Nephrology level of clinical authority, is always done (75%). In conclusion, there are still many particular actions according to the level of competence that is rare and cannot even be carried out because there are no such actions in outpatient installations. Keywords: Work Area, Clinical Authority, Competence